RELATIONSHIP OF SERUM RESISTIN WITH INSULIN RESISTANCE AND OBESITY - Zaidi, Syeda Ijlal Zehra; Shirwany, Tanvir Ali Khan (Journal of Ayub Medical College Abbottabad, 2015)
Background: Adipokines have been implicated in the modulation of insulin sensitivity and glucose tolerance and have thus gained importance in the study of Type 2 diabetes mellitus (T2DM). Resistin, a unique signalling molecule, is being proposed as a significant factor in the pathogenesis of obesity-related insulin resistance. However, its relevance to human diabetes mellitus remains uncertain and controversial. This study was therefore planned to compare and correlate the potential role of resistin in obese patients with T2DM and obese non-diabetic controls and also to evaluate the correlation between resistin and marker of obesity and glycaemic parameters. Methods: Fasting serum resistin, glucose and insulin were measured in forty obese diabetics (mean±SD BMI 35±5 kg/m2) and forty obese non-diabetics (mean±SD BMI 33±3 kg/m2). Insulin resistance was assessed using the HOMA-IR formula derived from fasting insulin and glucose levels. Results: Serum resistin levels (38±8 ng/ml) were significantly higher in type 2 diabetic patients as compared with the controls. Fasting blood glucose (164±46 mg/dl), serum insulin (37±7 µU/ml) and insulin resistance (19±8), were considerably higher among the studied diabetics than in the controls. Pearson’s correlation analysis revealed positive correlation between serum resistin and BMI (p=0.001) and HOMA-IR (p=0.561) in diabetic subjects. Similarly, a correlation also existed between serum resistin and BMI (p=0.016) and HOMA-IR (p=0.307) in control obese subjects. However, it was highly significant in diabetics as compared to non-diabetic controls. Conclusion: A significant BMI-dependent association exists between resistin and insulin resistance in patients with T2DM. It appears that resistin may play a role in the pathogenesis of obesity and insulin resistance and that both of these may contribute to the development of T2DM.